Inborn Errors of Metabolism in a Tertiary Pediatric Intensive Care Unit - Lipari, Patrícia; Shchomak, Zakhar; Boto, Leonor; Janeiro, Patrícia; Moldovan, Oana; Abecasis, Francisco; Gaspar, Ana; Vieira, Marisa (Journal of Pediatric Intensive Care, 2020)
Few studies exist describing resources and care of pediatric patients with inborn errors of metabolism (IEM) admitted to pediatric intensive care unit (PICU). This study aims to characterize the PICU admissions of these patients to provide better diagnostic and therapeutic care in the future. Retrospective analysis of pediatric patients with IEM admitted to the PICU of a tertiary care center at a metabolic referral university hospital from 2009 to 2019 was included. Clinical information and demographic data were collected from PICU clinical records. During this period, 2% (n = 88 admissions, from 65 children) out of 4,459 PICU admissions had clinical features of IEM. The median age was 3 years (range: 3 days–21 years) and 33 were male. Median age at diagnosis was 3 months; 23/65 patients with intoxication disorders, 21/65 with disorders of energy metabolism, 17/65 with disorders of complex molecules, and 4/65 with other metabolic diseases (congenital lipodystrophy, Menkes' disease, hyperammonemia without a diagnosis). From a total of 88 admissions, 62 were due to metabolic decompensation (infection—38, neonatal period decompensation—14, external accident—5, prolonged fasting—2, and therapeutic noncompliance—3) and 26 elective admissions after a scheduled surgery/elective procedure. The most frequent clinical presentations were respiratory failure (30/88) and neurological deterioration (26/88). Mechanical ventilation was required in 30 patients and parenteral nutrition in 6 patients. Extracorporeal removal therapy was required in 16 pediatric patients (12 with maple syrup urine disease and 4 with hyperammonemia) with a median duration of 19 hours. The median length of PICU stay was 3.6 days (3 hours–35 days). Eight patients died during the studied period (cerebral edema—2, massive hemorrhage—5, and malignant arrhythmia—1). Acute decompensation was the main cause of admission in PICU in these patients. The complexity of these diseases requires specialized human and technical resources, with an important impact on the recovery and survival of these patients.
Keywords: inborn errors of metabolism; pediatric intensive care unit; referral center